2007
DOI: 10.6026/97320630002157
|View full text |Cite
|
Sign up to set email alerts
|

Insilco analysis of functionally important residues in folate receptors

Abstract: Abstract:Lack of crystal structure data of folate binding proteins has left so many questions unanswered (for example, important residues in active site, binding domain, important amino acid residues involved in interactions between ligand and receptor). With sequence alignment and PROSITE motif identification, we attempted to answer evolutionarily significant residues that are of functional importance for ligand binding and that form catalytic sites. We have analyzed 46 different FRs and FBP sequences of vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…Tyrosines (non‐pY and pY) resulted among the most promiscuous residues, consistent with previous reports describing Y kinases as more promiscuous enzymes than S/T kinases [Brunati et al, 1989; Jia, 2008]. The conservation of predicted phosphoresidues among the nucleophosmin‐related sequences was high (median conservation of 84%) and comparable with those at other proteins [Eirin‐Lopez et al, 2006; Ramamoorthy et al, 2010]. The correlation analysis between conservation of these residues and their promiscuity showed that the most conserved ones (pT, non‐pT, and non‐pS) may be targeted by a small group of selected kinases.…”
Section: Discussionsupporting
confidence: 87%
“…Tyrosines (non‐pY and pY) resulted among the most promiscuous residues, consistent with previous reports describing Y kinases as more promiscuous enzymes than S/T kinases [Brunati et al, 1989; Jia, 2008]. The conservation of predicted phosphoresidues among the nucleophosmin‐related sequences was high (median conservation of 84%) and comparable with those at other proteins [Eirin‐Lopez et al, 2006; Ramamoorthy et al, 2010]. The correlation analysis between conservation of these residues and their promiscuity showed that the most conserved ones (pT, non‐pT, and non‐pS) may be targeted by a small group of selected kinases.…”
Section: Discussionsupporting
confidence: 87%
“…The α and β isoforms are glycosylphosphatidylinositol-anchored, whereas the γ isoform is a soluble protein constitutively secreted by lymphoid cells 2023. The most widely studied isoform is FRα, which is encoded for by the FOLR1 gene 24. The genes coding for FR, FOLR1–FOLR4 , are located on the long arm of chromosome 11 (q11.3–q13.5) 2527…”
Section: Folate Folate Receptors and Cancermentioning
confidence: 99%
“… 20 23 The most widely studied isoform is FRα, which is encoded for by the FOLR1 gene. 24 The genes coding for FR, FOLR1–FOLR4 , are located on the long arm of chromosome 11 (q11.3–q13.5). 25 27 …”
Section: Folate Folate Receptors and Cancermentioning
confidence: 99%